Decision Support System Uses The Prometheee Method to Determine Musrif and Musyrifah At The Center of Ma'had Al-Jamiah UIN Malang - Muhamad Tegar Maha Putra; Diah Arifah Pratiningtiyas; Yekti Asmoro Kanthi (Jurnal Teknologi dan Manajemen Informatika, 2020)
The Center for Ma'had Al-Jami'ah is a higher education institution that focuses on pure Islamic study programs located at UIN Malang. Every year, the Ma'had Al-Jami’ah Center opens registration for UIN Malang students who want to become musyrif and musyrifah. The definition of musyrifah comes from the word asyrafa-yusyrifu-isyrafan, which means to glorify, supervise, guide, control, give instructions, and approach. The person who carries out these responsibilities is called musyrif (son) and musyrifah (daughter). Students of UIN Malang semester 3 (three), 5 (five), and 7 (seven) who want to become musyrif or musyrifah must take a series of tests held by the Ma'had Al-Jami'ah center. To become musyrifah or musyrifah there are three phases of the test carried out namely: document test, written test, and interview test. At present the ma'had al-jami'ah center is still using a manual system in the recruitment of new musyrifs and musyrifahs, this makes the process of recruiting new musyrifs and musyrifahs inefficient and ineffective. Therefore, a system is needed to assist the process of recruiting musyrif and musyrifah at the ma'had al-jami’ah center. The system to be built will implement one of the methods of decision support systems. The decision support system used is the PROMETHEE method. DOI: https://doi.org/10.26905/jtmi.v6i1.3694